2015
DOI: 10.1073/pnas.1417262112
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and widespread occurrence of bioactive quinone pigments during post-Paleozoic crinoid diversification

Abstract: Secondary metabolites often play an important role in the adaptation of organisms to their environment. However, little is known about the secondary metabolites of ancient organisms and their evolutionary history. Chemical analysis of exceptionally well-preserved colored fossil crinoids and modern crinoids from the deep sea suggests that bioactive polycyclic quinones related to hypericin were, and still are, globally widespread in post-Paleozoic crinoids. The discovery of hypericinoid pigments both in fossil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…1 The fossil record indicates that crinoids are the most primitive of the present-day echinoderms, having flourished during both the Palaeozoic (544 -248 million years ago) and Mesozoic (248 -65 million years ago) Eras. 1,2 Their surviving descendants have hardly changed in their appearance. 1 Approximately 700 known species exist today, 3 typically existing in two forms: 'stalked' crinoids, or sea-lilies (representing approximately 100 known species, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 The fossil record indicates that crinoids are the most primitive of the present-day echinoderms, having flourished during both the Palaeozoic (544 -248 million years ago) and Mesozoic (248 -65 million years ago) Eras. 1,2 Their surviving descendants have hardly changed in their appearance. 1 Approximately 700 known species exist today, 3 typically existing in two forms: 'stalked' crinoids, or sea-lilies (representing approximately 100 known species, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…) in the next several decades, and is still ongoing (e.g. and references therein). This field has hardly been “neglected” (, p.1); in fact, a cursory literature database search under “fossil pigment” yields hundreds of references from the late 1800s to the present.…”
Section: The Role Of Pigments In Biology and Evolutionmentioning
confidence: 99%
“…The occurrence of trehalose as a major saccharide and the presence of sucrose in some samples imply that disaccharides can survive in sedimentary rocks as old as the Cretaceous. Other compounds like: isoprenoidal GDGTs (Schouten et al, 2003;Littler et al, 2011;Jenkyns et al, 2012), sterols (Melendez et al, 2013), hypericinoid pigments (Wolkenstein et al, 2008;Wolkenstein, 2015), polyketide-derived spiroborate pigments , or polar diterpenoids (Marynowski et al, 2007b) have been reported in Palaeozoic and Mesozoic sedimentary deposits. These are other groups of compounds previously thought as unstable which were preserved in pre-Palaeogene strata.…”
Section: Implications For Differences In Saccharide Distribution and mentioning
confidence: 99%